Genetic polymorphisms influencing antihypertensive drug responses - Jana El Cheikh (22330738) (2024)
Hypertension is a major contributor to cardiovascular disease and its associated morbidity and mortality. The low efficacy observed with some anti‐hypertensive therapies has been attributed partly to inter‐individual genetic variability. This paper reviews the major findings regarding these genetic variabilities that modulate responses to anti‐hypertensive therapies such as angiotensin converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARBs), diuretics, calcium channel blockers (CCBs) and β‐adrenoceptor blockers. The importance of studying these genetic polymorphisms stems from the goal to optimise anti‐hypertensive therapy for each individual patient, aiming for the highest efficacy and lowest risk of adverse effects. It is important to recognise that environmental and epigenetic factors can contribute to the observed variations in drug responses. Owing to the multigenic and multifactorial nature of drug responses, further research is crucial for translating these findings into clinical practice and the establishment of reliable recommendations. Other Information Published in: British Journal of Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/bph.17414